Efficacy of Monosodium Glutamate in the Australian Blowfly, Lucilia Cuprina Wiedmann (Diptera : Calliphoridae) (Bangladesh Journal of Zoology, 2012)
Efficacy of monosodium glutamate (MSG) was studied in the Australian blowfly, Lucilia cuprina at six different doses, viz. 0.5, 1, 2, 3, 5 and 10 g, and the results were compared with the control. The effects of MSG were observed on the mortality, width and histology of Malpighian tubules (MTs) of the fly. The highest (100%) and lowest (16.67%) mortalities of the  flies were recorded at 10g and 0.5g doses, respectively. Average widths of the  MTs of flies in treatment (5g dose) and control were 48.62 ?m and 58.85 ?m, respectively. Histological observations through the cross section of the MTs showed the constriction at 0.5g and 5g doses. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12896 Bangladesh J. Zool. 40(1): 69-75, 2012